The Development and Content of Movement Quality Assessments in Athletic Populations: A Systematic Review and Multilevel Meta-Analysis - Gyan A. Wijekulasuriya; Carl T. Woods; Aden Kittel; Paul Larkin (Sports Medicine - Open)
Abstract Background Despite their prominence in the sport and human movement sciences, to date, there is no systematic insight about the development and content of movement quality assessments in athletic populations. This is an important gap to address, as it could yield both practical and scientific implications related to the continued screening of movement quality in athletic contexts. Hence, this study aimed to systematically review the (i) developmental approach, (ii) movements included, (iii) scoring system utilised, and (iv) the reliability of movement competency assessments used in athletic populations. Methods Electronic databases (SPORTDiscus, MEDLINE, CINAHL, Web of Science, Scopus) were searched for relevant articles up to 12 May 2023. Studies were included if they reported data about the developmental approach, movements included, scoring system utilised and reliability of assessment in an athletic population. A modified Downs and Black checklist was used to measure study quality. Results From a total of 131 identified studies: (i) 26 (20%) described the developmental approach of an assessment; (ii) 113 (86%) included descriptions of the movements included; (iii) 106 (81%) included a description of scoring system and criteria; and (iv) 77 (59%) studies included reliability statistics. There were 36 assessments identified within these studies, comprising 59 movements in total. Each assessment scored movement quality through a Likert or binary classification system. Conclusion First, the results demonstrate that choosing an appropriate movement quality assessment in an athletic population may be a complex process for practitioners as the development approach, movements included and scoring criteria vary substantially between assessments. Second, academics could use these results to help design new assessments for novel applications that meet rigour and reliability requirements. Third, these results have the potential to foster guidelines of use for the reliable assessment of movement quality in athletic populations.